Analisis Persepsi Pengguna dengan Melihat Kualitas Layanan pada Aplikasi Mobile Transportasi Online - Inggar Tri Agustin Mawarni; Aji Prasetya Wibawa (Inovbiz: Jurnal Inovasi Bisnis, 2020)
The study was conducted to determine user perceptions of online transportation mobile applications by looking at PlayStore transportation mobile application analysis and user perceptions when using online transportation mobile applications. This research method is a qualitative method. This type of research uses informants, where direct users who use online mobile transportation applications and PlayStore observations as supporters. Data collection techniques carried out in the form of 1) interviews, 2) participant observation, 3) study documentation. The analysis method uses the interactive model of Mile and Hubermen with 4 stages, including collecting data, trying to formulate data or reduce data, after that the data presentation and drawing conclusions. The results showed that online mobile transportation applications have differences in improving service quality and in creating customer satisfaction. However, the observation of user perception shows that the Grab online transportation mobile application is considered to have superior quality and service than the Gojek and OK-Jack online transportation mobile application.